Mating System and Gene Flow Analysis within a Clonal Seed Orchard of Tectona grandis L.F. Using Microsatellite Markers - Pattanaik, S.; Shiva, K. (Indian Forester, 2017)
Microsatellite markers were used to analyze pollen dispersal and mating system within a clonal seed orchard of Tectona grandis. A total of 105 offsprings, five known seed bearers and 307 putative pollen donors were genotyped at four microsatellite loci. This dataset was analyzed using maximum likelihood approach to determine paternity of 105 offsprings. Spatial analysis of known seed bearers and identified pollen donors was used to trace pollen dispersal in this insect pollinated species. The analysis revealed the mating system to be dominated by cross fertilization (93.4%), with very low rate of selfing (6.6%). The average pollen dispersal distance varied from 84.0Â±18.8 m (SEM) to 153.4Â±14.2 m (SEM). About 80.7% of the pollen donors were beyond 50 m of the seed bearers. Of the thirty clones planted in the orchard, 23 participated in the breeding process. The number of pollen donors per seed tree varied from 10 to 14. Management implications of these findings are discussed in the paper.